iPod Fever: An Exploratory Study of Negative Symbolic Consumption in MP3 Player Market - Hsiao, Ching-Wei (2006)
This research is chiefly concerned with negative symbolic consumption which refers to consumers reject products and brands with negative symbolic meanings which are associated with negative self-concepts that they fear for. Since negative symbolic consumption has been an under-explored area in consumer research and the empirical study is limited in clothing industry, the objective of this study is specifically to explore and discuss the negative symbolic consumption in MP3 player market.